The Church and Catholic Higher Education - O'Brien, David J. (Horizons, 1990)
Recurrent debates about the church and higher education in the United States involve differing understandings of the nature and purpose of the church as well as differing understandings of the university. Catholic colleges and universities remain important but underutilized resources for the American church as it pursues its mission. Institutional, communitarian and servant models of the church must be examined more rigorously before they are used to prescribe changes in higher education. None is without problems. In a pluralistic and free society, a public church," self-consciously mediating the tensions between Christian integrity, Catholic unity, and civic responsibility, provides an altogether appropriate stance for Catholic colleges and universities as well. It points not to a neat resolution of outstanding difficulties but to ongoing dialogue among the publics to which both church and higher education must address themselves.